The role of demographic factors on workplace deviant behavior - Hadi Farhadi,; Fatimah Omar,; Rohany Nasir,; Maryam Zarnaghash, (Faculty of Social Sciences and Humanities, Universiti Kebangsaan Malaysia, 2015)
Workplace deviant behavior (WDB) has been a neglected topic in organizational researches. It refers to a range of volitional acts at work that harm or intend to harm organizations and their stakeholders, client, co-worker, customer, and supervisors. The main purpose of this study was to investigate the role of demographic factors (age, gender, education level, and organizational tenure) on deviant behavior in organizations. This study investigates whether subjects with different demographic background differs in tendency to deviant behavior. Two hundred twelve samples who were working as civil servant in Malaysia participated in this study. Data were collected using a set of questionnaire consisting of 30 items. The collected data were analyzed using SPSS software version 16.0. Although the findings of this study have shown differences in engaging in deviant behavior between subjects with different age and organization tenure level, it was unable to find differences in deviant behavior between subjects with different gender, and education levels. Study implications for practitioners and scientists in the field of industrial organizational psychology and future research were discussed as well.